Sustainable E-Bike Charging Station That Enables AC, DC and Wireless Charging from Solar Energy - Gautham Ram Chandra Mouli; Peter Van Duijsen; Francesca Grazian; Ajay Jamodkar; Pavol Bauer; Olindo Isabella (Energies, 2020)
If electric vehicles have to be truly sustainable, it is essential to charge them from sustainable sources of electricity, such as solar or wind energy. In this paper, the design of solar powered e-bike charging station that provides AC, DC and wireless charging of e-bikes is investigated. The charging station has integrated battery storage that enables for both grid-connected and off-grid operation. The DC charging uses the DC power from the photovoltaic panels directly for charging the e-bike battery without the use of an AC charging adapter. For the wireless charging, the e-bike can be charged through inductive power transfer via the bike kickstand (receiver) and a specially designed tile (transmitter) at the charging station, which provides maximum convenience to the user.